Pengaruh Penerapan Instrumen Performance Assessment pada Pembelajaran IPA Berbasis Laboratorium Real terhadap Hasil Belajar Siswa - Leli Hartina; Undang Rosidin; Agus Suyatna (Postgraduate, University of Mataram, 2020)
Abstract: The purpose of this research is to determine the effect of implementing performance assessment instruments on real laboratory-based science learning in students' learning outcomes. The sample of this research was the second grade students of SMP Negeri 3 Natar. The research design used was One Group Pretest-Posttest and One Shot Case Study. The research data was taken from the pre-test, post-test, and the Performance Assessment whose results were tested by using One Sample T-Test and Paired Sample T-Test. The results of One Sample T-Test showed that there was a significant effect on the confidence level of 95% of Performance Assessment instruments implementation on real laboratory-based science learning in psychomotor abilities as indicated by the average psychomotor abilities score >75. N-gain values obtained the average n-gain value of the pretest and posttest in students' cognitive abilities is 0,45 with medium criteria, so it can be concluded that there was an improvement in students' cognitive abilities after the learning process by using Performance Assessment instruments on real laboratory-based science learning and based on paired sample t-test there was a significant difference in the 95% confidence level between the average results of the pretest and posttest, which is 39,84 on the learning outcomes of cognitive abilities using Performance Assessment instruments. Keywords: Performance Assessment Instrument, Real Laboratory, Students' Learning Outcomes.